2013
DOI: 10.2217/fon.13.115
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Properties of RANKL/RANK in Cell Differentiation, Proliferation and Metastasis

Abstract: It is known that there are close relationships between bone destruction and tumor growth in bone metastasis. RANKL is a central factor in bone metastasis, inducing osteoclastogenesis mediated by its receptor RANK. Recent reports demonstrate that RANKL has important roles in organogenesis stimulating proliferation and differentiation of epithelial and stroma cells. RANKL is induced not only by cytokines and hormones but also by UV-irradiation, inflammation and carcinogens. Expression of RANK and RANKL is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 123 publications
0
11
0
2
Order By: Relevance
“…Mice deficient in RANK are not capable of lactation owing to lack of functional mammary gland formation during pregnancy (19). RANKL is also important to the formation of mammary glands by stimulating the proliferation of epithelial cells through nuclear factor kappa B (NF-kB); progesterone was important for this process through induction of RANKL (20). In a mouse mammary tumor virus model, direct action of RANKL was observed in tumorigenesis, which was accelerated by progesterone (21).…”
Section: Cell Growth and Differentiationmentioning
confidence: 99%
“…Mice deficient in RANK are not capable of lactation owing to lack of functional mammary gland formation during pregnancy (19). RANKL is also important to the formation of mammary glands by stimulating the proliferation of epithelial cells through nuclear factor kappa B (NF-kB); progesterone was important for this process through induction of RANKL (20). In a mouse mammary tumor virus model, direct action of RANKL was observed in tumorigenesis, which was accelerated by progesterone (21).…”
Section: Cell Growth and Differentiationmentioning
confidence: 99%
“…RANKL‐RANK interaction induces activation of the TNF receptor‐associated factor 6 (TRAF6), which leads to activation of MAPKs (ERK, JNK, and p38) and several transcription factors including c‐fos. (Kukita & Kukita, ; Takayanagi, ). This signaling results in the activation of nuclear factor of activated T cells (NFAT) c1, a master regulator of osteoclastogenesis (Asagiri & Takayanagi, ; Ishida et al, ; Takayanagi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of osteoclasts involves several factors such as receptor activator of nuclear factor-kappaB (NF-kappaB) ligand (RANKL) and macrophage colony-stimulating factor (Novack, 2011). Many researchers have shown that RANKL is directly involved in the differentiation of macrophages into osteoclasts (Wang et al, 2003;Kukita and Kukita, 2013). RANKL is able to activate mature osteoclasts (Burgess et al, 1999), and induce osteoclast polarization and hypercalcemia (Xu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%